PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID TENTANG PRINSIP DASAR ANIMASI DENGAN METODE LUTHER-SUTOPO: DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA FOR CLASS XI MULTIMEDIA SMKN 40 JAKARTA USING LUTHER-SUTOPO METHOD - Akbar Dwipangga; M. Ficky Duskarnaen; Hamidillah Ajie (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
A good, creative, and interesting learning media can increase studentsâ€™ interest in learning. A good learning media can also make easier for teacher to deliver material to students. Unfortunately, in the Basic Principles of Animation material in class XI Multimedia SMKN 40 Jakarta, students have difficulty accepting and understanding the material because the learning media is less attractive and the delivery is monotonous by teacher. To overcome this problem, the development of learning media in the form of Android-based applications for the Basic Principles of Animation material uses the Luther-Sutopo method which produces an Android-based application which is expected to help students understand the material. Product feasibility testing was carried out by material experts with a feasibility level of 100% with the feasibility category "Very Eligible", testing by media experts with a feasibility level of 98.7% with the eligibility category "Very Eligible", and testing by respondents with a feasibility level of 93.4% with â€œVery Eligibleâ€ category of eligibility. The developed Android-based application can be stated to be very suitable for use as a learning media to help students class XI Multimedia SMKN 40 Jakarta receiving and understanding the Basic Principles of Animation material.